Forms and Shadows: A Cognitive-Poetic Reading of Charles Williams’s Fiction - Kowalczyk, Andrzej Slawomir (Peter Lang GmbH, 2017)
This book is a cognitive-poetic study of the seven novels of Charles Williams (1886–1945), a British author of spiritual fiction and non-fiction, a poet, playwright and a literary critic. It approaches his multidimensional narratives with reference to cognitive phenomena and mechanisms such as the figure-ground organization, conceptual metaphors, conceptual blending, image schemata, scripts, cognitive narrative frames, narrative spaces, cognitive deixis, and empathy. The methodology not only stresses the role of the reader’s conceptual and emotional involvement in the building of the story-worlds, but also reveals the novels’ polyphonic character.
10.3726/b11520
Keywords: Williams; Charles; Kognitive Poetik; Roman; Spiritualität